Challenging Easter Island's collapse: the need for interdisciplinary synergies - Rull, Valentí; Cañellas-Boltà, Núria; Saez, Alberto; Margalef, Olga; Bao, Roberto; Pla-Rabes, Sergi; Valero-Garcés, Blas; Giralt, Santiago (Frontiers in Ecology and Evolution, 2013)
The reigning paradigm holds that Easter Island suffered an eco-societal collapse (ecocidal or not) sometime in the last millennium, prior to European contact (AD 1720). We discuss some novel palaeoecological and archaeological evidence that challenges this assumption. We use this case study to propose a closer collaboration between archaeology, palaeoecology and palaeoccology. This collaboration allows us to unravel historical trends in which both environmental changes and human activities might have acted, alone or coupled, as drivers of ecological and societal transformations. We highlight a number of particular points in which scholars from disparate disciplines, working together, may enhance the scope and the soundness of historical inferences. These points are the following: 1) the timing of the initial Easter Island colonisation and the origin of the settlers, 2) the pace of ecological and societal transformations since that time until the present, and 3) the occurrence of potential climate-human synergies as drivers of eco-societal shifts.